Characterization of tetraethylene glycol passivated iron nanoparticles - Nunes, Eloiza da Silva [UNESP]; Viali, Wesley Renato [UNESP]; Silva, Sebastiao William da; Huamani Coaquira, Jose Antonio; Garg, Vijayendra Kumar; Oliveira, Aderbal Carlos de; Morais, Paulo Cesar; Jafelicci Júnior, Miguel [UNESP] (Elsevier B.V., 2014)
The present study describes the synthesis and characterization of iron@iron oxide nanoparticles produced by passivation of metallic iron in tetraethylene glycol media. Structural and chemical characterizations were performed using transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and Mossbauer spectroscopy. Pomegranate-like core@shell nanoparticulate material in the size range of 90-120 nm was obtained. According to quantitative phase analysis using Rietveld structure refinement the synthesized iron oxide was identified as magnetite (Fe3O4) whereas the iron to magnetite mass fractions was found to be 47:53. These findings are in good agreement with the data obtained from Mossbauer and thermal gravimetric analysis (TGA). The XPS data revealed the presence of a surface organic layer with higher hydrocarbon content, possibly due to the tetraethylene glycol thermal degradation correlated with iron oxidation. The room-temperature (300K) saturation magnetization measured for the as-synthesized iron and for the iron-iron oxide were 145 emu g-1 and 131 emu g-1, respectively. The measured saturation magnetizations are in good agreement with data obtained from TEM, XRD and Mossbauer spectroscopy. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Iron@iron oxide; Core@shell; Magnetic nanoparticle; Metallic iron; Nanoparticles; Polyol